lepidium-like, a Naturally Occurring Mutant of Capsella bursa-pastoris, and Its Implications on the Evolution of Petal Loss in Cruciferae - Klepikova, Anna V.; Shnayder, Elina D.; Kasianov, Artem S.; Remizowa, Margarita V.; Sokoloff, Dmitry D.; Penin, Aleksey A. (Frontiers in Plant Science, 2021)
Naturally occurring mutants whose phenotype recapitulates the changes that distinguish closely related species are of special interest from the evolutionary point of view. They can give a key about the genetic control of the changes that led to speciation. Here we describe lepidium-like (lel), a naturally occurring variety of an allotetraploid species Capsella bursa-pastoris that is characterized by the typical loss of all four petals. In some cases, one or two basal flowers in raceme had one or two small petals. The number and structure of other floral organs are not affected. Our study of flower development in the mutant showed that once initiated, petals either cease further development and cannot be traced in anthetic flowers or sometimes develop to various degrees. lel plants showed earlier beginning of floral organ initiation and delayed petal initiation compared to the wild type plants. lel phenotype has a wide geographical distribution, being found at the northern extremity of the species range as well as in the central part. The genetic analysis of inheritance demonstrated that lel phenotype is controlled by two independent loci. While the flower in the crucifer family generally has a very stable structure (four sepals, four petals, six stamens and two carpels), several deviations from this ground plan are known, in particular in the genus Lepidium. Capsella bursa-pastoris is an emerging model for the study of polyploidy (which is also very widespread in Cruciferae); the identification and characterization of the apetalous mutant lays a foundation for further research of morphological evolution in polyploids.